Emergent many-body composite excitations of interacting spin-1/2 trimers - Anup Kumar Bera; S. M. Yusuf; Sudip Kumar Saha; Manoranjan Kumar; David Voneshen; Yurii Skourski; Sergei A. Zvyagin (Nature Communications, 2022)
It was recently predicted that, in addition to well-known spinon excitations, a 1D spin-trimer chain with periodic exchange couplings hosts novel composite excitations. Bera et al. experimentally demonstrate and characterize such excitations, termed doublons and quartons, in a spin-trimer compound Na2Cu3Ge4O12.